Study of knowledge, attitude and practice among nurses regarding needle stick and sharp item injuries - ., Sonia; Singh, Sukhbir; Singh, Brijender; Singh, Satpal; Khurana, Anil; Verma, Ramesh (International Journal Of Community Medicine And Public Health, 2019)
Background: Needle stick injuries are an important occupational hazard for nursing personnel as they form an important mechanism for transmission of blood borne pathogens. A needle stick injury (NSI) is defined as an accidental skin-penetrating stab wound from a hollow-bore needle (or any sharp) containing another person’s blood or body fluid. Sharp injury (SI) is defined as a skin-penetrating stab wound caused by sharp instruments & accidents in a medical setting. Methods: The study is hospital based cross-sectional descriptive in PGIMS Rohtak. The study was designed towards achievement of all objectives. The study was carried out from 14 June 2016 to 13 August 2016. Results: Majority (6%) of sample were in the age group of 20-25 years and (31%) in age group of 26-30 years. Majority of sample (98.5%) were female. Majority of sample (90%) were GNM, (6.5%) were B.Sc Nursing, (1.5%) was M.sc Nursing. Majority of sample (91.5%) were married. Conclusions: The study identified the presence of suboptimal practices that put both staff nurses and patients at significant risk of contracting occupational infections.